PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA PELAJARAN KEAMANAN JARINGAN MATERI FIREWALL MIKROTIK PADA SISWA KELAS XI TKJ DI SMK NEGERI 1 TENGGARONG - Miftah Ar-Rizqy, Muhammad; Rosita, Dewi; Nirawana, I Wayan Sugianta (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Learning In Network Security, Particularly the Topic of Mikrotik Firewall, Often Poses a Challenge for Students Due To the Complexity of the Material and The Limited Availability of Engaging Learning Media. Conventional Methods Such as Textbooks Have Not Been Effective Enough in Bridging Theory and Practice. Therefore, This Study Aims to Develop an Interactive Learning Medium in The Form of An Instructional Video Based on The ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) To Help 11th-Grade TKJ (Computer and Network Engineering) Students at SMK Negeri 1 Tenggarong Understand the Material More Easily and Engagingly. The Video Development Process Involves Several Stages: Needs Analysis, Storyboard Design, Production Using Adobe Premiere, And Feasibility Evaluation. The Video Content Is Based on Official Teaching Modules and Is Designed to Be Accessible Via Smartphones or Computers Online Through Cloud Drive. To Enhance Visual Appeal, The Video Includes Animations and GIF Images. Feasibility Tests Were Conducted by Media Experts, Subject Matter Experts, And Through a Trial Involving 36 Students. The Results Show That the Instructional Video Falls into The Highly Feasible Category, With an Average Score Of 4.39 From Media Experts, 4.29 From Subject Matter Experts, And 4.44 From Students. Overall, The Learning Media Received an Average Score Of 4.37. The Study Recommends Further Development in Terms of Content, Video Quality, And Editing Aspects to Produce Learning Media That Is More Optimal and Easier for Students to Understand.